(Epi)genetic profiling of extraembryonic and postnatal tissues from female monozygotic twins discordant for Beckwith–Wiedemann syndrome. Issue 9 (6th July 2020) - Fontana, Laura; Bedeschi, Maria F.; Cagnoli, Giulia A.; Costanza, Jole; Persico, Nicola; Gangi, Silvana; Porro, Matteo; Ajmone, Paola F.; Colapietro, Patrizia; Santaniello, Carlo; Crippa, Milena; Sirchia, Silvia M.; et al.
Abstract: Background: Beckwith–Wiedemann syndrome (BWS) is an overgrowth disorder caused by defects at the 11p15.5 imprinted region. Many cases of female monozygotic (MZ) twins discordant for BWS have been reported, but no definitive conclusions have been drawn regarding the link between epigenetic defects, twinning process, and gender. Here, we report a comprehensive characterization and follow‐up of female MZ twins discordant for BWS. Methods: Methylation pattern at 11p15.5 and multilocus methylation disturbance (MLID) profiling were performed by pyrosequencing and MassARRAY in placental/umbilical cord samples and postnatal tissues. Whole‐exome sequencing was carried out to identify MLID causative mutations. X‐chromosome inactivation (XCI) was determined by HUMARA test. Results: Both twins share KCNQ1OT1:TSS‐DMR loss of methylation (LOM) and MLID in blood and the epigenetic defect remained stable in the healthy twin over time. KCNQ1OT1:TSS‐DMRLOM was nonhomogeneously distributed in placental samples and the twins showed the same severely skewed XCI pattern. No MLID‐causative mutations were identified. Conclusion: This is the first report on BWS‐discordant twins with methylation analyses extended to extraembryonic tissues. The results suggest that caution is required when attempting prenatal diagnosis in similar cases. Although the causative mechanism underlying LOM remains undiscovered, the XCI pattern and mosaic LOM suggest that both twinning and LOM/MLID occurred after XCI commitment. Abstract :